Precision Medicine in the Diagnosis and Management of Orthopedic Biofilm Infections - Rossella Baldan; Parham Sendi; Parham Sendi; Parham Sendi; Parham Sendi (Frontiers in Medicine, 2020)
Orthopedic biofilm infections are difficult to treat and require a multidisciplinary approach to diagnostics and management. Recent advances in the field include methods to disrupt biofilm, sequencing tools, and antibiotic susceptibility tests for bacteria residing in biofilm. The observation of interclonal differences in biofilm properties of the causative microorganisms, together with considerations of comorbidities and polypharmacy in a growing aging population, calls for a personalized approach to treat these infections. In this article, we highlight aspects of precision medicine that may open new perspectives in the diagnosis and management of orthopedic biofilm infections.